2019
DOI: 10.3389/fneur.2019.00628
|View full text |Cite
|
Sign up to set email alerts
|

Presurgical Functional Cortical Mapping Using Electromagnetic Source Imaging

Abstract: Preoperative localization of functionally eloquent cortex (functional cortical mapping) is common clinical practice in order to avoid or reduce postoperative morbidity. This review aims at providing a general overview of magnetoencephalography (MEG) and high-density electroencephalography (hdEEG) based methods and their clinical role as compared to common alternatives for functional cortical mapping of (1) verbal language function, (2) sensorimotor cortex, (3) memory, (4) visual, and (5) auditory cortex. We hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 185 publications
(220 reference statements)
0
9
0
Order By: Relevance
“…Lastly, our results are proof-of-concept that intraoperative functional brain mapping could be more efficient with machine learning. Conventional passive (non-stimulation) mapping of functionally significant motor areas uses modulation of a predefined frequency band, commonly gamma (Kreidenhuber et al, 2019). Using an SVM or similar spectrogram-based classification would be more accurate because it includes a wider range of frequencies, including and extending beyond the predefined band.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, our results are proof-of-concept that intraoperative functional brain mapping could be more efficient with machine learning. Conventional passive (non-stimulation) mapping of functionally significant motor areas uses modulation of a predefined frequency band, commonly gamma (Kreidenhuber et al, 2019). Using an SVM or similar spectrogram-based classification would be more accurate because it includes a wider range of frequencies, including and extending beyond the predefined band.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated high concordance between MEG-based language mapping and invasive procedures (eg, intracarotid amobarbital procedure or Wada), favoring MEG as a noninvasive option for language mapping and lateralization. 10,[15][16][17][18] A key transformative step is the integration of source-modeled MEG data with MR imaging to yield MSI, either by the overlay of single equivalent dipole sources or by statistical mapping of either spontaneous or event-related changes. 19,20 This renders MEG data directly interpretable by the neuroradiologist in a fashion very analogous to fMRI, but combining both mapping of functional, eloquent cortex, as well as the sources of interictal spontaneous discharges (dysfunctional MR imaging).…”
Section: Current Indications For Meg and Magnetic Source Imagingmentioning
confidence: 99%
“…), the Wada test has the additional disadvantage of not being able to localize cortical language function and is therefore not suitable as a diagnostic tool for more precise surgical planning. 40,41 To the best of our knowledge, we present the first case series of pediatric patients in whom preoperative nTMS mapping data were combined with nTMS-based DTI fiber tracking to enhance surgical safety for children undergoing brain surgery in functionally eloquent areas. Fortunately, we did not observe any new postoperative neurological deficit in these cases.…”
Section: Figmentioning
confidence: 99%